Auto raise hand in Microsoft teams (API/Extension) - Teh, Boon Hin (2023)

(untitled)
This project is working on a growing trend – Artificial Intelligence. To be more specific, it is regarding facial expression recognition based on deep learning. Artificial Intelligence focuses on developing intelligences of machines, by developing algorithms, machines are able to learn from data and patterns, even perform tasks that require human intelligence, such as visual perception, speech recognition, and decision-making. Facial expression recognition is one of the popular topic in computer vision as its extensive applicability in various fields. In spite of that, people are becoming concerned about the issues brought about by deep learning as the trend expands at a staggering pace. For example, efficiency, accuracy, data confidentiality, user-friendliness and so on. This is a research based project for academic purposes which aims to investigate methods on training a CNN model with better performance that is applicable to project – auto raise hand API/extension in Microsoft Teams. Three systems related to the project are selected for reviewing their technology used, strengths, weaknesses, with some suggestions provided. The reviewed products are MorphCast, FaceReader, and Live 3D. After reviewing, the project scope is defined and there are three objectives to be archived in this project. The proposed solution is to develop a high performance CNN model. Also, the hardware and software requirements to conduct this project are listed and briefly introduced.